2014
DOI: 10.1007/s11606-014-2926-6
|View full text |Cite
|
Sign up to set email alerts
|

Walking Cadence and Mortality Among Community-Dwelling Older Adults

Abstract: The ability to walk ≥100 steps∙minute(-1) predicts a reduction in mortality among a sample of community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 28 publications
1
30
0
3
Order By: Relevance
“…Specifically, for each 10 steps per minute increase in cadence there was a 40% lower likelihood of meaningful decline in usual gait speed.Among NHANES participants a cadence that was ten steps per minute faster was associated with a 4% decrease in all-cause mortality and the ability to walk 100 steps per minute was associated with a reduction in cardiovascular related deaths (Brown, Harhay, & Harhay, 2014). In the latter case it is not clear if cadence is simply a gait characteristic or actually a marker for cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for each 10 steps per minute increase in cadence there was a 40% lower likelihood of meaningful decline in usual gait speed.Among NHANES participants a cadence that was ten steps per minute faster was associated with a 4% decrease in all-cause mortality and the ability to walk 100 steps per minute was associated with a reduction in cardiovascular related deaths (Brown, Harhay, & Harhay, 2014). In the latter case it is not clear if cadence is simply a gait characteristic or actually a marker for cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence of a benefit of LTPA with regard to CVD mortality is to some extent controversial. Men with the ability to walk more than 100 steps per minute had lower CVD mortality than those who could not, and physical activity was associated with lower CVD mortality in a 4‐year follow‐up of British men . Another study found a 34% lower risk of CVD mortality in a follow‐up study of 9,518 community‐dwelling white women aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and high levels of LTPA have been shown to reduce all‐cause mortality in older men and women . In addition, walking, a specific form of LTPA, has been found to be associated with lower risk of all‐cause mortality Apparently, even occasional physical activity reduces the risk of all‐cause mortality in older adults …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance was characterized by the cadence of the longest locomotion period, and the number of locomotion bouts longer than 30 steps with cadence equal or superior to 100 steps/min, that may correspond to outdoor purposeful activity [21][22][23] (expressed as % of the total number of locomotion bouts).…”
Section: Methodsmentioning
confidence: 99%